DEVELOPMENT OF COMPOSITE MATERIALS FOR CORROSION PROTECTION OF MAIN GAS AND OIL PIPELINES WITH INCREASED CHEMICAL ADHESION - Urinov, Abrorbek; Kadirxanov, Jamshid (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
At present, during new construction of trunk oil pipelines, as well as during re-insulation of existing pipelines for their anti-corrosion protection, various insulation materials and protective coating designs are used, ranging from bituminous-mastic trace application to multilayer polymer coatings of factory application. But with all the variety of protective coatings available, it is practically impossible to make a choice in favor of only one universal coating that would meet all requirements and provide effective corrosion protection of pipelines under various construction and operating conditions.